2021
DOI: 10.3390/jcm10153240
|View full text |Cite
|
Sign up to set email alerts
|

Whether a Gluten-Free Diet Should Be Recommended in Chronic Autoimmune Thyroiditis or Not?—A 12-Month Follow-Up

Abstract: Elimination diets have recently become extremely popular among people with autoimmune diseases. A gluten-free diet is indicated in celiac disease (CD), but some studies show its effectiveness in cases of autoimmunity. The aim of this study was to assess whether the use of a gluten-free diet is also effective in patients with chronic autoimmune thyroid disease (cAITD), which is the most common thyroid autoimmune pathology associated with chronic inflammation, over-reactivity of the immune system, auto-destructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…The control group’s diet contained gluten, and the study group was on a gluten-free diet for 12 months. During follow-up, there was a significant reduction in TSH levels in the study group [ 151 ]. Only a few studies suggest that gluten elimination may be helpful for some HT patients.…”
Section: Diet In Htmentioning
confidence: 99%
“…The control group’s diet contained gluten, and the study group was on a gluten-free diet for 12 months. During follow-up, there was a significant reduction in TSH levels in the study group [ 151 ]. Only a few studies suggest that gluten elimination may be helpful for some HT patients.…”
Section: Diet In Htmentioning
confidence: 99%
“…In contrast, antithyroid antibody levels did not improve. [1] Due to the presence of randomization, the larger group of subjects, the longer duration of the study, and the verification that the patients do not have coexisting celiac disease, it can be concluded that the 2021 study appears to be the most authoritative.…”
Section: Relationship Between Gluten-free Diet and Hashimoto's Diseas...mentioning
confidence: 99%
“…This is also important for the absorption of levothyroxine in the gut. [1] However, it is important to keep in mind the frequent co-occurrence of celiac disease in these patients. It is in these patients that dietary modification is warranted, as well as in patients with gluten sensitivity.…”
Section: List Of Referencesmentioning
confidence: 99%
See 2 more Smart Citations